A smart storage optimisation technique on the cloud. (2017) - Nuaimi, Klaithem Al; Mohamed, Nader; Nuaimi, Mariam Al; Al-Jaroodi, Jameela
This paper is an extension to a recent work on enhancing load balancing and optimising storage consumption on the cloud. Our methodology, called ssCloud (Smart Storage Cloud), is based on methods designed to enhance the load balancing in concurrent file download techniques on the cloud using a collaborative dual direction technique. In this paper, we show how ssCloud operates in both the upload and download phases for providing Data as a Service (DaaS) on the cloud. Our goal is to reduce the amount of storage consumed on the cloud while providing a fast and efficient download time for the cloud clients. This is done by having two separate cloud interfaces, one for download requests (load balancing module) and another for upload requests, which involves partitioning and saving files on the available cloud servers (FileController). We also provide an analysis of ssCloud performance and compare it to other reviewed storage optimisation techniques on the cloud by simulating the cloud environment and comparing service times.